The Effect of Noise Produced by High Speed Handpiece on Predental Anxiety and Heart Rate in Patients Visiting a Dental Hospital in Attarkhel - Joshi, Rojin; Gautam, Suman; Joshi, Barsha; Khapung, Anju (Nepal Medical College Journal, 2025)
Dental anxiety is a very common dental health problem in the populations of many countries and the prevalence of dental anxiety has been the subject of many studies. The etiology of this condition may be due to previous traumatic experiences, such as severe pain or discomfort during or after a dental procedure and negative observations by the dentist. Noise produced by high speed handpiece can also cause dental anxiety. This cross sectional study was conducted to assess the effect of noise produced by high speed handpiece on predental anxiety and heart rate. The Modified Dental Anxiety Scale (MDAS) measuring tool was filled before the start of the treatment by the patients to measure their general dental anxiety score. The patients were divided into two groups; experienced and non-experienced. The heart rate was recorded with the help of a pulse oximeter at three different intervals i.e. before, during and after the procedure. Descriptive statistics was calculated along with Chi square test, ANNOVA, Independent t test were used. Anxiety was associated with prior treatment experience and the result was statistically significant. Majority of study participants had low anxiety (59.2%), 10.7% had no anxiety and only 2.4% had extreme anxiety. The relation between heart rate with gender (M: 62.4%, F: 56.6%), age (18-29 years: 55.6%, 30-39 years: 67.6%, 40-50 years: 61.8%) and prior treatment experience (experienced: 67.0%, non-experienced: 51.5%) was statistically insignificant. It was concluded that non-experienced group had more anxiety than the experienced group. The percentage of heart rate was more during the treatment compared to before treatment and after treatment.